PENGARUH PENGGUNAAN METODE BERNYANYI TERHADAP PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB SISWA MADRASAH TSANAWIYAH - Damayanti, Tari; Dardiri, Ahmad; Dzul Iman, Maman (Journal of Islamic Studies, 2023)
The purpose of this study was to determine the ability of Arabic vocabulary in class VII students of MTS Al-Zaytun using the singing method and not, and to determine the effect of using the singing method on the madrasa students' ability to master Arabic vocabulary. In this quantitative study, researchers collected data using observation, testing, and documentation data collection techniques. The results showed that after the pretest and posttest obtained from the multiple sample t test for the experimental category with a t value of -13.124 <2.024. Thus Ho is rejected and H1 can be accepted. The conclusion is that the singing method greatly influences the improvement of Arabic vocabulary mastery of class VII students of MTS Al-Zaytun Indramayu.